IMPROVEMENT OF THE NOTIFICATION AND EVACUATION SYSTEM FOR CHILDREN WITH HEARING IMPAIRMENTS IN EDUCATIONAL INSTITUTIONS - Shcholokov Е.; Rashkevіch N.; Maiboroda, R.; Otrosh, Yu. (Municipal economy of cities. Series: «Economy science», 2025)
The study is aimed at improving the system of warning and evacuation management for children with hearing impairments in fire conditions. This is important for ensuring the safety of inclusive education in educational institutions. The research analyzed the technology used in warning and evacuation management systems for children with special educational needs. Technologies for warning and evacuation management systems for children with special educational needs are based on the use of different types of stimulation. Traditional sound signals are effective for people with normal hearing, but do not provide the proper level of safety for children with hearing impairments. In such cases, tactile technologies play an important role, in particular vibrating beds and devices that create a sense of alarm through touch. Visual aids, such as light indicators, flashing lights and "running" light tracks, contribute to orientation in conditions of smoke and darkness. The most effective approach is the integration of various technologies, which allows creating a multi-channel alert and evacuation system adapted to the needs of children with special educational needs, ensuring their safety in educational institutions. The main requirements for the alert and evacuation management system for children with hearing impairments are the use of inclusive alert methods, such as vibrating devices and light alarm signals to ensure their safety. Be automated with intelligent functions for rapid adaptation of the evacuation route depending on the circumstances. It is important to train staff and children, as well as provide technical control and maintenance of the system to guarantee its reliability. The system should be flexible and adaptable to different educational institutions, taking into account the specific needs of children. The main elements of the proposed alert and evacuation management system for children with hearing impairments are light indicators, flashing paths, vibrating devices, which allow for rapid transmission of danger signals. Additionally, automation of the operation of these devices is provided by synchronizing them with the fire alarm system and a centralized control panel.